Traditional and Contemporary Protected areas for Wildlife Conservation in Meghalaya, India - Singha, Haorangbam Arundeep; Bisht, Madho S. (Indian Forester, 2023)
Traditional ways of protection and conservation of wildlife, forests and all the natural resources have been suppressed by colonialism, industrialization and a new knowledge system resulting in the biodiversity loss. Then came the new concept of â€œprotected areasâ€ for the conservation and protection of wildlife after the establishment of first National Park, Yellowstone, US in 1872. Even then the threats to wildlife remained or rather increased in a newer form of poaching, habitat disturbances, etc. The model of human-exclusivity (National Parks, Wildlife Sanctuaries, Reserved Forest) is being met with several challenges, favouring the creation of more human-inclusive protected areas that were traditionally present (before establishment of first National Park in 1872) and are now left in a few places like in the State of Meghalaya, due to the provisions of the Sixth Schedule of the Indian Constitution. Meghalaya has both, traditional and contemporary methods of forest management and wildlife conservation and protection. This study clearly indicates that human-inclusive methods (that is traditional forest management) of wildlife and nature conservation need to be maintained and incorporated along with the contemporary methods of wildlife conservation.